Global issues in agricultural development - Rosegrant, Mark W.; Fan, Shenggen; Otsuka, Keijiro (International Food Policy Research Institute, 2021)
Chapter 1 reviewed dynamically changing global trends in agricultural development and identified emerging and diverse issues associated with the process of global agricultural development. This chapter reviews the literature on these topics in order to clarify the context under which regional issues (Part II), newly arising critical issues (Part III), and future challenges and opportunities (Part IV) are discussed. More specifically, this chapter addresses the major debates around agricultural development, policies, and technological changes to reduce or eliminate food insecurity and attain sustainable development.